PENGARUH KOMPENSASI FINANSIAL, LINGKUNGAN KERJA NON FISIK DAN KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PT. BPR SINAR PUTERAMAS - Made Yoga Pratama; I Wayan Gede Supartha (Cross-border, 2023)
Bank Perkreditan Rakyat or abbreviated as BPR are bank financial institutions that carry out activities based on Syariah Principles which in their activities do not provide services in payment traffic. BPR only carry out activities in the form of deposits in the form of time deposits, savings, and other forms that channel funds as a BPR business. Companies need quality human resources so that employee motivation increases and company goals are achieved. This research was conducted at PT. BPR Sinar Puteramas, Klungkung Regency. This study used a sample of 32 employees using a non-probability sampling method with a saturated sample technique, collected through interviews and questionnaires using multiple linear regression analysis techniques, classical assumption test, model feasibility test (F test) and partial test (T test). Financial compensation, non-physical work environment, and leadership have a significant positive effect on work motivation. Based on the results of the simultaneous significance test (F test) obtained a significance value of 0.000 F. A significant value of 0.000 <0.05 means that financial compensation, non-physical work environment, and leadership are thought to have a significant effect on work motivation.